PENGARUH PENENTUAN LOKASI TERHADAP KESUKSESAN USAHA JASA BERSKALA MIKRO/KECIL - Wisnu Adhi Putra; Nana Nawasiah; Murti Widyaningsih (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
Business location is a place where companies produce goods or services that focus on the economy. The development of a company is determined by one important factor, namely location decision. The purpose of this study is to determine the effect of location decision (based on business environment conditions, infrastructure availability, and location costs) on business success. Data collection in this study was carried out through observation, interviews, and distributing questionnaires to several micro/small scale copy center business owners in Jagakarsa, South Jakarta. Analysis of the data in this study uses multiple linear regression analysis. This study provides results that the condition of the business environment, the availability of infrastructure, and location costs have a positive and significant effect both partially and simultaneously on business success. Therefore, as an effort to achieve and increase business success, business owners must consider the condition of the business environment, the availability of infrastructure, and location costs when determining/choosing a business location.